Hey! listen to this : stories to read aloud - Trelease, Jim. (New York, NY, USA : Penguin Books, 1992)
A collection of fairy tales, folklore, and famous stories from around the world arranged for reading aloud.
Tell me a story!: The Gunniwolf, retold by Wilhelmina Harper -- Little Green Riding Hood, by Gianni Rodari -- Wolf Story, by William McCleery -- Tales from long ago: Noah's Friends, by Marc Gellman -- The Tortoise and the Hare, retold from Aesop -- School days: Sideways Stories from Wayside School, by Louis Sachar -- Ramona the Pest, by Beverly Cleary -- Child of the Silent Night, by Edith Fisher Hunter -- Family Secrets, by Susan Shreve -- Food for thought: Bavsi's Feast, by Adèle Geras -- Chocolate Fever, by Robert Kimmel Smith -- Homer Price, by Robert McCloskey -- Families: Alexander, by June Epstein -- Mr. Popper's Penguins, by Richard and Florence Atwater -- The Stories Julian Tells, by Ann Cameron -- The Fish Angel, by Myron Levoy -- Nadia the Willful, by Sue Alexander -- Greyling, by Jane Yolen -- Folk and fairy tales: Unanana and the Elephant, retold by Kathleen Arnott -- The Tales of Uncle Remus, retold by Julius Lester -- The Indian Cinderella, retold by Cyrus Macmillan -- Shen of the Sea, retold by Arthur Bowie Chrisman -- The Emperor's New Clothes, retold from Hans Christian Andersen -- The Search for the Magic Lake, by Genevieve Barlow -- The Magic Thread -- Animal tales: The Tale of Peter Rabbit, by Beatrix Potter -- Charlotte's Web, by E.B. White -- Bambi, by Felix Salten -- Black Beauty, by Anna Sewell -- Lassie Come-Home, by Eric Knight -- Where the Red Fern Grows, by Wilson Rawls -- Gentle Ben, by Walt Morey -- Gigantic creatures: The Story of Giant Kippernose, by John Cunliffe -- The Reluctant Dragon, by Kenneth Grahame -- The Moon's Revenge, by Joan Aiken -- Fantasy lands: Ozma of Oz, by L. Frank Baum -- The Lion, the Witch and the Wardrobe, by C.S. Lewis -- James and the Giant Peach, by Roald Dahl -- Children of courage: The Boy Who Stopped the Sea, retold by Louis Untermeyer -- The Courage of Sarah Noble, by Alice Dalgliesh -- The Sign of the Beaver, by Elizabeth George Speare -- I Have a Dream: The Story of Martin Luther King, Jr., by Margaret Davidson -- Orphans of the storm: Sara Crewe, by Frances Hodgson Burnett -- The Story of Holly and Ivy, by Rumer Godden -- Understood Betsy, by Dorothy Canfield Fisher -- Classic tales: The Golden Touch, retold from Nathaniel Hawthorne -- The Pied Piper, retold from Joseph Jacobs and Andrew Lang, with poetry by Robert Browning -- Aladdin and the Wonderful Lamp, retold from Andrew Lang.
"A Penguin original"--Cover.
Includes bibliographical references (page 412).
Keywords: Children's literature; Short stories; Juvenile works; Short stories; Children's literature